Efecto de un bioestimulante proveniente de la industria azucarera sobre el crecimiento y rendimiento del cultivo de pitahaya amarilla (Selenicereus megalanthus) - Cedeño Giraldo, Jordan Joel (2023)
The purpose of this research was to evaluate a biostimulant from the sugar industry on the growth and yield of the yellow pitahaya (Selenicereus megalanthus) crop. 30 posts or experimental unit were evaluated in the CIIDEA area (City of Agricultural Research, Innovation and Development) of the Polytechnic Campus of ESPAM-MFL (Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López). A "Student's t" distribution statistical design was used for paired samples. The treatments applied were: With Biostimulant (T1) and Without Biostimulant (T2). The results obtained according to the growth variable (shoot length, number of shoots, number of flowers), in the rainy and dry seasons did not present a significant difference (p>0.05). Compared to the yield variable (fruit diameter (mm), fruit firmness (kg/f), Brix degrees of the fruit, fruit weight (g), fruit length (cm)), there were no significant differences (p >0.05).